Blood Flow Restriction Training for the Intervention of Sarcopenia: Current Stage and Future Perspective - Zhang, Xu-zhi; Xie, Wen-qing; Chen, Lin; Xu, Guo-dong; Wu, Li; Li, Yu-sheng; Wu, Yu-xiang (Frontiers in Medicine, 2022)
Sarcopenia is a geriatric syndrome that is characterized by a progressive and generalized skeletal muscle disorder and can be associated with many comorbidities, including obesity, diabetes, and fracture. Its definitions, given by the AWGS and EWGSOP, are widely used. Sarcopenia is measured by muscle strength, muscle quantity or mass and physical performance. Currently, the importance and urgency of sarcopenia have grown. The application of blood flow restriction (BFR) training has received increased attention in managing sarcopenia. BFR is accomplished using a pneumatic cuff on the proximal aspect of the exercising limb. Two main methods of exercise, aerobic exercise and resistance exercise, have been applied with BFR in treating sarcopenia. Both methods can increase muscle mass and muscle strength to a certain extent. Intricate mechanisms are involved during BFRT. Currently, the presented mechanisms mainly include responses in the blood vessels and related hormones, such as growth factors, tissue hypoxia-related factors and recruitment of muscle fiber as well as muscle satellite cells. These mechanisms contribute to the positive balance of skeletal muscle synthesis, which in turn mitigates sarcopenia. As a more suited and more effective way of treating sarcopenia and its comorbidities, BFRT can serve as an alternative to traditional exercise for people who have marked physical limitations or even show superior outcomes under low loads. However, the possibility of causing stress or muscle damage must be considered. Cuff size, pressure, training load and other variables can affect the outcome of sarcopenia, which must also be considered. Thoroughly studying these factors can help to better determine an ideal BFRT scheme and better manage sarcopenia and its associated comorbidities. As a well-tolerated and novel form of exercise, BFRT offers more potential in treating sarcopenia and involves deeper insights into the function and regulation of skeletal muscle.